"I Fell into Librarianship": Experiences of Post-Soviet Librarians at the National Academic Library in Astana, Kazakhstan. (2nd April 2016) - Emmelhainz, Celia; Bukhtoyarova, Darya
ABSTRACT: This paper explores the attitudes of librarians in post-Soviet Kazakhstan regarding their roles at the new National Academic Library of the Republic of Kazakhstan (NAL). Using ethnographic observation, interviews, and surveys of library staff (n = 24), we find that Kazakhstani librarians either sensed a "calling" to librarianship or "fell into" library careers given life circumstances, and value their library for its contribution to cultural preservation and digital access on a national scale. This pilot project presents NAL to an international community, sharing the voices of Russian- and Kazakh-speaking librarians to highlight the role of libraries in the development of the post-Soviet nation.